2003
DOI: 10.1021/ja028692+
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structure of Self-Assembled Monolayers of Alkanethiolates on Palladium

Abstract: The adsorption of n-alkanethiols onto polycrystalline thin films of palladium containing a strong (111) texture produces well-organized, self-assembled monolayers. The organization of the alkane chains in the monolayer and the nature of the bonding between the palladium and the thiol were studied by contact angle measurements, optical ellipsometry, reflection absorption infrared spectroscopy (RAIRS), and X-ray photoelectron spectroscopy (XPS). The XPS data reveals that a compound palladium-sulfide interphase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
417
3
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(471 citation statements)
references
References 38 publications
39
417
3
12
Order By: Relevance
“…They discussed the results based on the effect of SAMs structure on wetting. These seminal works, and others [8,10,12,23,24], showed that monolayers on silver and gold were more reproducible than on copper in part due to morphological changes that occur due to oxidation and/or subsequent desorption of the alkanethiol. Therefore, most studies of interface structure-property relationships in wetting of monolayers has focused on SAMs formed on silver and gold.…”
Section: The Original Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They discussed the results based on the effect of SAMs structure on wetting. These seminal works, and others [8,10,12,23,24], showed that monolayers on silver and gold were more reproducible than on copper in part due to morphological changes that occur due to oxidation and/or subsequent desorption of the alkanethiol. Therefore, most studies of interface structure-property relationships in wetting of monolayers has focused on SAMs formed on silver and gold.…”
Section: The Original Studiesmentioning
confidence: 99%
“…This self-assembly process is a mechanism by which disordered small building units spontaneously arrange into large, ordered phases [5]. Many self-assembled systems have been investigated, with monolayers of alkanethiolates on gold or silver being the most studied SAM systems to date [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with prior work demonstrating stronger interaction of Pd with thiols compared with Au and Pt. 26 Following these findings, we used electrodeposition through the lithographically defined apertures to reduce palladium ions in solution in order to produce metallic nanostructures, filling the apertures with metal structures that fan out above the top surface of the oxide as shown in the SEM images in Figs. 1͑b͒ and 1͑c͒.…”
Section: Integrated Nanostructures For Direct Detection Of Dna At Attmentioning
confidence: 99%
“…This is somewhat surprising, as ODT is a longer molecule than DDT (a 18 C atom chain versus a 12 C atom chain) and hence forms a thicker SAM than DDT (about 30%). 38,39 On the other hand, the nature (i.e., the length of the molecules) of the SAM can influence the molecular packing. It has been shown by STM that a lack of structure occurs for n-alkanethiolate (C n H 2n+2 ) SAMs of 16 < n < 28 with even n values, (Figure 2).…”
Section: Resultsmentioning
confidence: 99%